2003
DOI: 10.1111/1539-6975.00062
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Risk, Insurance, and Actuarial Research: Citations From 1996 to 2000

Abstract: This article evaluates the relative significance of research published in 16 risk, insurance, and actuarial journals by examining the frequency of citations in these risk, insurance, and actuarial journals and 16 of the leading finance journals during the years 1996 through 2000. First, the article provides the frequency with which each sample risk, insurance, and actuarial journal cites itself and the other sample journals so as to communicate the degree to which each journal's published research has had an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(53 citation statements)
references
References 27 publications
4
45
4
Order By: Relevance
“…Colquitt () extends Colquitt () to evaluate citations appearing in the sample journals between 1996 and 2000. He also adds three risk journals to the Colquitt () study to bring the total sample journals to 32.…”
Section: Prior Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Colquitt () extends Colquitt () to evaluate citations appearing in the sample journals between 1996 and 2000. He also adds three risk journals to the Colquitt () study to bring the total sample journals to 32.…”
Section: Prior Literaturementioning
confidence: 99%
“…This percentage (22) is calculated using data reported in table of Colquitt () and (), and table of Colquitt et al. ().…”
mentioning
confidence: 99%
“…"As noted in Colquitt (2003), it is entirely possible that the cause for a high self-citation index might be that the journal publishes research that is of a specialized nature, the type not commonly found in the other sample journals. "…”
Section: Introductionmentioning
confidence: 99%
“…Related studies in this area have been conducted through the years by Colquitt (1997Colquitt ( , 2003Colquitt ( , 2005, Colquitt and D'Arcy (2009), and Colquitt et al (1998). The main focus there was on the quality and influence of the journals themselves and the articles they contain, rather than on the performance of countries and institutions.…”
Section: Introductionmentioning
confidence: 99%